ANALISIS IKLIM ORGANISASI, KEPEMIMPINAN DAN PENGARUHNYA TERHADAP KINERJA PEGAWAI PADA PT. PLN (Persero) JASA SERTIFIKASI - Hotifatruwosa, Desty; Yuningsih, Erni (Fakultas Ekonomi Universitas Djuanda, 2015)
The research objectives are: 1) knowing organizational climate, leadership and employee performance; 2) the effect of organizational climate and leadership partially on employee performance; 3) the effect of organizational climate and leadership simultaneously on organizational performance. The population in this study were all employees amounted to 75 people with a sampling method using Non-Profitability Sampling (random sampling). Data collection techniques with questionnaires, interviews and observations while data analysis techniques using multiple linear regression analysis, correlation analysis, coefficient of determination analysis and statistical test (F test and T test). Results of the research is that there is a strong relationship between organizational climate and leadership with employee performance. The coefficient of determination shows that the organizational climate and leadership contributed 62.6%, while 37.4% are influenced by other factors such as the system of compensation, organizational structure, job design and reward systems. Based on statistical test concluded that organizational climate and leadership simultaneously and partially real effect on employee performance.Keywords: organizational climate, leadership, performance